Internet censorship detected in Egypt (Egypt) - Voidly (Voidly Global Censorship Index, 2026)
WARNING severity censorship detected in Egypt. Data sourced from CensoredPlanet.
Censorship Incident ID: EG-2026-0415. Severity: warning. Confidence: 65%